Ambient Noise Monitoring during Pure-Tone Audiometry - Margolis, Robert H.; Saly, George L.; Wilson, Richard H. (Journal of the American Academy of Audiology, 2022)
Background There is an increasing need to administer hearing tests outside of sound-attenuating rooms. Maximum permissible ambient noise levels (MPANLs) from published in standards (Occupational Health and Safety Administration [OSHA] 1983; American National Standards Institute [ANSI] S3.1–1999 (R2018)) can be modified to account for the additional attenuation provided by circumaural earphones (relative to supra-aural earphones) that are used for pure-tone audiometry. Ambient noise can influence the results of pure-tone audiometry by elevating thresholds by direct masking and by producing distractions that affect the accuracy of the test. The effects of these distractions have not been studied in relation to pure-tone audiometry in adult listeners.Purpose In Part I MPANLs provided by ANSI and OSHA standards are extended to account for the greater attenuation provided by circumaural earphones. Rules (“alerts”) were developed taking into account the listeners' thresholds. In Part II effects of distracting noise on pure-tone thresholds are reported.Methods and Results In Part I MPANLs two standards were modified for circumaural earphones by adding the additional attenuation provided by three circumaural earphones (relative to supra-aural earphones). A set of rules (“alerts”) is provided for identifying masking effects from ambient noise in a variety of conditions (earphone type, threshold elevation, uncovered ear). In Part II the distracting effects of an industrial noise sample on thresholds obtained from five listeners with normal hearing are described. Pure-tone thresholds were measured in quiet and in distracting noise presented at various levels. The effects of the distracting noise on the following variables were measured: time per trial, number of trials required to measure threshold, threshold shift, and perceived distractibility of the noise. Time per trial was unaffected by distracting noise. Number of trials required for threshold, threshold shift, and perceived distractibility increased with distracting noise level.Conclusion Part I: The modified MPANLs provide more relevant determinations of the potential effects of ambient noise on pure-tone thresholds than the values in the standards. Part II: Distracting noise affects pure-tone threshold measurements in a manner that is different from direct masking. The potential contaminating effect of distracting noise can be measured and reported.
Keywords: ambient noise; circumaural earphone; distractibility; maximum permissible ambient noise level; pure-tone audiometry; supra-aural earphone